191 Performance at Medical School and Foundation Programme Selection Can Predict Success in The MRCS Examination. (4th May 2021) - Ellis, R; Scrimgeour, D; Brennan, P; Lee, A; Cleland, J
Abstract: Background: Identifying factors that predict success in the Membership of the Royal College of Surgeons (MRCS) examination can aid trainees' exam preparation and help deaneries identify candidates likely to require additional support. We assessed whether performance at Medical School and UK Foundation Programme selection (Educational Performance Measurement (EPM) and Situational Judgement Test (SJT)) predicted MRCS success. Method: We analysed data from the UKMED Database for UK graduates who had attempted MRCS Part A ( n =  1, 975) and Part B ( n =  630) between 2013-2017. Univariate analysis examined the relationship between performance and the likelihood of passing MRCS at first attempt. Logistic regression identified independent predictors of MRCS success. Results: Each additional EPM decile increased the chances of passing MRCS by 52% for Part A (odds ratio 1.52 [95% confidence interval 1.46-1.60]) and 27% for Part B (1.27 [1.18-1.38]). Each EPM point awarded for degrees increased the likelihood of passing Part A by 29% (1.29 [1.12-1.48]). SJT score was not a statistically significant independent predictor of MRCS success ( P >0.05). Conclusions: This is the first study to investigate the relationship between UK medical school performance and postgraduate surgical exam success. Higher ranked students are more likely to succeed in the MRCS compared to their lower ranked peers.